On Formulating Strategic Problems - Ramaprasad, Arkalgud; Mitroff, Ian I. (Academy of Management Review, 1984)
An understanding of the development of logico-mathematical structures (LMSs) is needed to explain, predict, and improve the process of formulating a strategic problem, and consequently to improve the formulation of the problem. Based on Piaget's (1974) model of development of a LMS, a model of the development of an LMS for a strategic problem is presented; the relationship between Jungian (Jung, 1924) personality typology and development of LMSs is discussed; and implications for strategic management are given.